Railway Bridge Using Small Post-Tensioned Concrete Box Girder - Inkyu Rhee (The Baltic Journal of Road and Bridge Engineering)
A girder depth is the critical parameter for rapid construction of bridge and clearance limitation in urban area such as high-density residential district. A standard post-tensioned I-shaped concrete girder usually demands relatively higher girder depth in order to retain sufficient moment arm between compressive and tensile fiber. To elaborate this issue, a small rectangular hollowed section can be used as a replacement of I-shaped standard girder. This small post-tensioned concrete box girder allows more flexible girder depth adjustment rather than standard I-shaped posttensioned girder plus additional torsion resistance benefits of closed section. A 30 m long, 1.7 m high and 3.63 m wide actual small post-tensioned concrete box girder is designed. A laboratory test was performed for its static behaviors by applying 6400 kN amount of load in the form of 4-point bending test. The load-deflection curve and crack patterns at different loading stage are recorded. In addition, to extract the dynamic characteristics; natural frequency and damping ratio of this girder, several forced vibration tests using oscillator are carried out with varying operational frequency. Nonlinear finite element analysis of this 4-point bending test under monotonic static load is discussed with the aid of concrete damaged plasticity using ABAQUS program. Finally, a series of modal dynamic analyses of different span length and girder depth of small post-tensioned girder bridge is performed in order to validate the applicability to railway bridge and compared to the UIC design criteria in the form of time dependent dynamic responses such as deflection, acceleration and end rotation.